2018
DOI: 10.1016/j.appet.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Children's self-regulation of eating provides no defense against television and online food marketing

Abstract: Exposure to unhealthy food marketing stimulates children's food consumption. A child's responsiveness is influenced by individual factors, resulting in an increased vulnerability to advertising effects among some children. Whether these differential responses may be altered by different parental feeding behaviours is unclear. The purpose of this study was to determine the relationship between parental feeding practices and children's food intake responses to food advertising exposure. A randomised, crossover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(51 reference statements)
1
17
0
4
Order By: Relevance
“…Even though this association was not significant in the multivariate analysis, it echoes findings of previous studies [23,25]. Although well-intentioned, restrictive dietary practices may incur opposite consequences, and are associated with child weight gain, a higher attraction, preference and consumption of restricted foods, and the habit of eating even in the absence of hunger [9][10][11]21,23,26,27]. The use of restriction as a practice of control is usually chronic and continuous, and leads the child to lose the ability to regulate the innate sensations of hunger and satiety, resulting in the increased consumption of restricted foods when they are available [8,25,27].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Even though this association was not significant in the multivariate analysis, it echoes findings of previous studies [23,25]. Although well-intentioned, restrictive dietary practices may incur opposite consequences, and are associated with child weight gain, a higher attraction, preference and consumption of restricted foods, and the habit of eating even in the absence of hunger [9][10][11]21,23,26,27]. The use of restriction as a practice of control is usually chronic and continuous, and leads the child to lose the ability to regulate the innate sensations of hunger and satiety, resulting in the increased consumption of restricted foods when they are available [8,25,27].…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, pressuring a child to eat can mask their internal signs of hunger and satiety, which leads children to regulate their eating habits through external stimulation, such as predetermined times for meals and fixed size of portions [7,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy food adverts were not found to increase children's consumption of fruit or vegetables . Parental behaviour, such as perceived encouragement to be thin or controlling feeding practices, was reported to affect susceptibility to the effects of television advertising on dietary intake . Two studies conducted in Georgia and Mexico found no association between television advertising and energy intake …”
Section: Resultsmentioning
confidence: 95%
“…Childhood obesity has become a global issue in the 21st century, with children worldwide affected by the “double burden” of malnutrition and associated consequences for children’s health and well-being [ 1 , 2 , 3 ]. Marketing for unhealthy, ultra-processed foods and beverages (usually conceptualised as those high in saturated fat, sugar or salt; henceforth, “unhealthy food”) is well evidenced as a factor in children’s food preferences, purchases and eating [ 3 , 4 , 5 , 6 , 7 ]. Marketing exposure prompts the eating of extra items, raising calorie intake that is not compensated for later, and this has a sustained impact over time [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%